Indigenous identity and metropolitan domination in selected novels by Najuib Mahfouz and David Malouf - Al-Areqi, Rashad Mohammed (2008)
This study explores the impact of British metropolitan power on reshaping the indigenous identity through analysing selected literary works by Mahfouz and Malouf. Despite the great efforts of the postcolonial countries to decolonise their lands from the British military occupation and their success in driving the colonisers outside of their borders, they did not succeed to separate themselves from the culture of the British power that extended to encompass the aspects of indigenous identity represented by cultural, social, political and religious creeds. Through the postcolonial and psychoanalytic theories and by analysing and comparing the main themes and characterisations of selected works by Mahfouz and Malouf, the researcher highlights the impact of the British metropolitan power on reshaping the indigenous identity represented by hybridity and hegemony, dislocation and unhomeliness, exile and alienation, nationalism and resistance. Both novelists, Mahfouz and Malouf, have their own understanding related to the impact of the British metropolitan power on the indigenous people due to the differences in the structure of their communities. Thus, this study proves that the British metropolitan power triumphs its victory over Egypt while it fails to achieve its objectives in Australia as depicted in the selected works.